Neurogenic pulmonary edema following Cryptococcal meningoencephalitis associated with HIV infection. Issue 4 (7th May 2015) - Kondo, Reiichiro; Sugita, Yasuo; Arakawa, Kenji; Nakashima, Shinji; Umeno, Yumi; Todoroki, Keita; Yoshida, Tomoko; Takase, Yorihiko; Kage, Masayoshi; Oshima, Koichi; Yano, Hirohisa
<x xml:space="preserve">Abstract</x> Neurogenic pulmonary edema (NPE) is a clinical syndrome characterized by the acute onset of pulmonary edema following a significant central nervous system insult. Only a few cases of NPE after Cryptococcal meningitis have been reported. We report a case of NPE following Cryptococcal meningoencephalitis. A 40‐year‐old man with no medical history was hospitalized for disturbance of consciousness. Blood glucose level was 124 mg/dL. Non‐contrast head computed tomography showed no abnormalities. Lumbar puncture revealed a pressure of over 300 mm H2O and cerebrospinal fluid (CSF) confirmed a white blood cell count of 65/mm3. The CSF glucose level was 0 mg/dL. The patient was empirically started on treatment for presumptive bacterial and viral meningitis. Four days after, the patient died in a sudden severe pulmonary edema. Autopsy was performed. We found at autopsy a brain edema with small hemorrhage of the right basal ganglia, severe pulmonary edema and mild cardiomegaly. Histologically, dilated Virchow‐Robin spaces, crowded with Cryptococci were observed. In the right basal ganglia, Virchow‐Robin spaces were destroyed with hemorrhage and Cryptococci spread to parenchyma of the brain. No inflammatory reaction of the lung was seen. Finally, acute pulmonary edema in this case was diagnosed as NPE following Cryptococcal meningoencephalitis. After autopsy, we found that he was positive for serum antibodies to human immunodeficiency virus.